Composites of Reduced Graphene Oxide Based on Silver Nanoparticles and Their Effect on Breast Cancer Stem Cells - Babu Vimalanathan; Devasena Thiyagarajan; Ruby Nirmala Mary; Magesh Sachidanandam; Savarimuthu Ignacimuthu; Dhanavathy Gnanasampanthapandian; Johnson Rajasingh; Kanagaraj Palaniyandi (Bioengineering)
Graphene and its related nanocomposites have garnered significant interest due to their distinct physiochemical and biological properties. In this study, reduced graphene oxide–silver hybrid nanostructures were synthesized for applications in biomedical nanotechnology, particularly in targeting cancer stem cells (CSCs). A range of analytical techniques, such as X-ray diffraction (XRD), Raman spectroscopy, Fourier-transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), and UV–visible absorption spectroscopy (UV–VIS), were employed to characterize graphene oxide (GO), reduced graphene oxide (rGO)–silver nanoparticles (AgNPs), and their composite structures. The GO-rGO-AgNPs exhibited potent anticancer properties as evidenced by cell culture assays, spheroid formation assay, and quantitative RT-PCR analysis. Treatment of breast cancer cells (MCF-7) with GO, rGO, and AgNPs significantly reduced cell proliferation and mammosphere formation. Furthermore, these treatments downregulated the expression of marker genes associated with CSCs in MCF-7 cells. Among the tested materials, rGO-AgNP, sodium citrate-mediated GO-AgNP, and rGO-AgNP nanocomposites demonstrated superior inhibitory effects on cell survival compared to GO alone. These findings suggest that these nanocomposites hold promise as effective and non-toxic therapeutic agents for targeting cancer cells and CSCs, thereby offering a novel approach to cancer treatment.